5LP- INCREASE WORK EFFICIENCY BY CHANGING TO LINTERING EQUIPMENT (Journal of Science-Innovative Research in Uzbekistan, 2023)
To improve the efficiency of the 5LP type linting equipment by adding a filter and placing a mesh surface to separate small impurities from seeded cotton. The linting we offer is a linting process that comes after the ginning process. 5LP in this process aims to separate the impurities by applying a stringer surface to the linter equipment